Altered sulcogyral patterns of orbitofrontal cortex in patients with mild cognitive impairment. (30th August 2020) - Wang, Zixiang; Zhang, Xin; Liu, Renyuan; Wang, Yang; Qing, Zhao; Lu, Jiaming; Obeso, Ignacio; Zhang, Bing; Li, Yansong
Highlights: Enhanced prevalence of orbitofrontal sulcogyral pattern Type II in MCI patients compared with healthy controls. Reduced prevalence of orbitofrontal sulcogyral pattern Type I in MCI patients compared with health controls. Suggests that atypical orbitofrontal sulcogyral patterns may be one of a potential neurodevelopmental risk marker of MCI. Abstract: Mild cognitive impairment (MCI) is increasingly recognized as a risk factor for Alzheimer's disease (AD). Neuroimaging studies have revealed structural abnormalities in the orbitofrontal cortex (OFC) in MCI patients, while other findings fail to report anatomical alterations. Accordingly, structural changes in this brain region amongst MCI patients has not been well characterized. Given that OFC sulcogyral organization has increasingly been demonstrated as a reliable pre-morbid marker of pathological conditions in several neuropsychiatric disorders, we examined the distribution of OFC sulcogyral patterns (classified into Type I, II and III) based on structural brain data from 68 MCI patients and 55 healthy controls. Our results, supported by both Frequentist and Bayesian statistics, showed that MCI patients exhibited an increased prevalence of Type II pattern compared with healthy controls, particularly in the right hemisphere. Meanwhile, MCI patients showed a decreased prevalence of Type I pattern compared with healthy controls. Taken together, our results reveal a skewed distribution of OFC sulcogyral in MCI patients, possibly reflecting a potential neurodevelopmental risk marker of MCI.